Effects of B0 eddy currents on imaging isocenter shifts in 0.35‐T MRI‐guided radiotherapy (MR‐IGRT) system. Issue 6 (12th April 2021) - Curcuru, Austen N.; Lewis, Benjamin C.; Kim, Taeho; Yang, Deshan; Michael Gach, H.
Abstract : Purpose: The purpose of this study was to measure gantry angle‐related eddy currents in a 0.35‐T MRI‐Linac and determine if B0 (zeroth order) eddy currents are the primary cause of gantry angle‐dependent imaging isocenter shifts vs other potential causes like B0 inhomogeneities and gradient (first order) eddy currents. For conventional Cartesian acquisitions, B0 eddy currents can cause imaging isocenter shifts along both phase encode and readout directions. Gradient eddy currents can cause spatial distortion along both the phase encode and readout directions. Center frequency offsets can cause imaging isocenter shifts along the readout direction that vary with readout gradient polarity. Methods: MRI‐related eddy currents and imaging isocenter shifts were measured on a 0.35‐T MRI‐Linac at gantry angles from 0° to 330° in increments of 30 ° . All measurements were made after gradient shimming and center frequency tuning at each planned gantry angle. Eddy current and field homogeneity measurements were conducted using a 24‐cm diameter spherical phantom. Gradient and B0 eddy currents were calculated from the free induction decays (FIDs) resulting from selective excitation of slices located ±5 cm from isocenter. B0 eddy currents were also calculated from FIDs acquired with nonselective excitation and compared with B0 eddy current values derived using selective excitation. B0 inhomogeneities and center frequency offsets were measured by acquiring FIDs with nonselective excitation. Imaging isocenter shifts were measured using a 33x33x10.5 cm 3 uniformity linearity (grid) phantom and a 3D true fast imaging with steady‐state precession (TrueFISP) sequence used in MRI‐guided radiation therapy. Eddy currents were compared to vendor specifications and correlated with the imaging isocenter shifts. Measurements were conducted before and after the MRI‐Linac's waveguide was replaced with an updated design to reduce eddy currents. Results: B0 eddy currents were highly correlated (r = 0.986, P  << 0.001) for measurements made with vs without selective excitation. Transverse (X and Y) axis B0 eddy currents before and after the waveguide upgrade were out of specification (specification: ≤0.1 μT m/mT for delays < 10 ms) for most of the measured gantry angles. Gradient eddy currents before and after the upgrade were within specifications for the measured gantry angles (≤0.1% for delays < 10 ms). B0 eddy currents and imaging isocenter shifts were highly correlated (r = 0.965, P  << 0.001). After the Linac waveguide upgrade, root mean square (RMS) peak B0 and gradient eddy currents dropped 45% and 11%, respectively, for delays <10 ms, while imaging isocenter shifts dropped 53%. Isocenter shifts were observed in both phase encode and readout directions. Center frequency offsets were <26 Hz while B0 inhomogeneities were <33 Hz full width at half maximum (FWHM). Conclusions: Imaging isocenter shifts measured in a 0.35‐T MRI‐Linac were highly correlated with B0 eddy currents. The eddy currents and imaging isocenter shifts decreased after the MRI‐Linac's waveguide was replaced.